Falanges ungueais de crocodilomorfos da Bacia Bauru(Cretáceo Superior, Brasil) - Ismar de Souza Carvalho; João Tadeu Arruda; Oscar Rocha-Barbosa; Felipe Mesquita de Vasconcellos (Anuário do Instituto de Geociências, 2004)
ungual phalanxes of recent crocodylomorphs are modifiedinto queratin covered claws. They are conical, ventrally curved with asharp distal end. They are used during locomotion, digging and femalesizing on copula. Nevertheless, fossil crocodylomorphs claws present awider morphological and functional diversity. It was analysed fossil clawsfrom the Late Cretaceous rocks of Adamantina (General Salgado County)and Marília (Uberaba County) Formations of the Bauru Basin. Theclaws found in the Adamantina Formation were associated with skeletalremains of a baurusuchid. They are laterally compressed, more ventrallycurved and stronger than those of recent crocodylomorphs. They alsopresent, at their base, many furrows related to muscle attachment. Theclaws found in the Marília Formation were associated to the remains ofa peirosaurid. They show a great lateral compression and a blade-likeventral edge. They also present a slight ventral curvature and strongfurrows in their base for muscle attachment. The morphological dataobtained from these claws allow the investigation of the autoecology ofthese Cretaceous crocodylomorphs. Keywords: ungual phalanxes of recent crocodylomorphs are modifiedinto queratin covered claws. They are conical, ventrally curved with asharp distal end. They are used during locomotion, digging and femalesizing on copula. Nevertheless, fossil crocodylomorphs claws present awider morphological and functional diversity. It was analysed fossil clawsfrom the Late Cretaceous rocks of Adamantina (General Salgado County)and Marília (Uberaba County) Formations of the Bauru Basin. Theclaws found in the Adamantina Formation were associated with skeletalremains of a baurusuchid. They are laterally compressed, more ventrallycurved and stronger than those of recent crocodylomorphs. They alsopresent, at their base, many furrows related to muscle attachment. Theclaws found in the Marília Formation were associated to the remains ofa peirosaurid. They show a great lateral compression and a blade-likeventral edge. They also present a slight ventral curvature and strongfurrows in their base for muscle attachment. The morphological dataobtained from these claws allow the investigation of the autoecology of these Cretaceous crocodylomorphs.